Numerical Study of Gas-Sand Two-Phase Flow Erosion in a Standard 90° Elbow - Nauman Khan; Muhammad Rehan Khan; Sati Ullah; Tariq Talha; Muhammad Ali Khan; Zubair Sajid (Engineering Proceedings, 2023)
Erosive wear is a common problem in hydrocarbon industry pipelines transporting a multi-phase flow. Erosion is more critical in flow-changing devices, like tees, elbows, U- bends, valves, and chokes. By performing numerical simulations, this research investigation focuses on pre-eminent parameters that influence elbow wear, including erodent size and flow velocity. In this analysis, particle diameters of 150 and 300 μm and velocities of 11, 15, and 23 m/s were used. At a velocity of 11 m/sec, the erosion rate induced by a particle size of 300 μm was 1.62 times higher than with a particular size of 150 μm. Similarly, when the velocity was increased from 15 m/s to 23 m/s for the same particle size of 300 μm, the erosion rate was increased by 3.23 times.